BIRTHING BALL MENEKAN INTENSITAS NYERI PADA IBU BERSALIN KALA I - Maternity, Dainty (Ikatan Bidan Indonesia (IBI), 2022)
Data released by the Directorate of Maternal Health Development in 2012 showed that maternal mortality in Indonesia is caused by several factors. These factors include bleeding (30.1%), hypertension (26.9%), infection (5.6%), prolonged labor (1.8%), abortion (1.6%) and other causes (34.5%). Based on these data, prolongedlabor is one of the contributing factors to the maternal mortality rate in Indonesia, even though the percentage is quite small. The purpose of this study is to determine the effectiveness of giving birth balls to the stage 1 labor pain in active phase maternity in the Working Area of the TalangJawa Inpatient Health Center in 2021.This research was quantitative, quasi-experimental research design with an approach using pretest-posttest control group design. The study population was mothers who gave birth in the working area of TalangJawa Inpatient Health Center based on estimates from the birth interpretation in May-July 2021 totaling 68 people. Data analysis was univariate and bivariate with independent t-test.The average labor pain in the group given the birth ball before the intervention with a mean of 57.00 and after the intervention with a mean value of the first measurement is 62.67 and the second measurement is 68.93. The average labor pain in the group that was not given the birth ball pretest with a mean of 50.80, the mean value of the first measurement was 75.40 and the second measurement was 88.80. The results of the statistical test obtained a P-value = 0.000, which means that there is an effectiveness of giving birthballs to labor pain in maternity mothers in the working area of TalangJawa Inpatient Health Center in 2021.